A Clinical Drug‐Drug Interaction Study Assessing a Novel Drug Transporter Phenotyping Cocktail With Adefovir, Sitagliptin, Metformin, Pitavastatin, and Digoxin. Issue 6 (12th August 2019) - Trueck, Christina; Hsin, Chih‐hsuan; Scherf‐Clavel, Oliver; Schaeffeler, Elke; Lenssen, Rebekka; Gazzaz, Malaz; Gersie, Marleen; Taubert, Max; Quasdorff, Maria; Schwab, Matthias; Kinzig, Martina; Sörgel, Fritz; et al.
Abstract : A new probe drug cocktail containing substrates of important drug transporters was tested for mutual interactions in a clinical trial. The cocktail consisted of (predominant transporter; primary phenotyping metric): 10 mg adefovir‐dipivoxil (OAT1; renal clearance (CLR )), 100 mg sitagliptin (OAT3; CLR ), 500 mg metformin (several renal transporters; CLR ), 2 mg pitavastatin (OATP1B1; clearance/ F ), and 0.5 mg digoxin (intestinal P‐gp, renal P‐gp, and OATP4C1; peak plasma concentration (Cmax ) and CLR ). Using a randomized six‐period, open change‐over design, single oral doses were administrated either concomitantly or separately to 24 healthy male and female volunteers. Phenotyping metrics were evaluated by noncompartmental analysis and compared between periods by the standard average bioequivalence approach (boundaries for ratios 0.80–1.25). Primary metrics supported the absence of relevant interactions, whereas secondary metrics suggested that mainly adefovir was a victim of minor drug‐drug interactions (DDIs). All drugs were well tolerated. This cocktail may be another useful tool to assess transporter‐based DDIs in vivo .